Adherence to prophylaxis in adolescents and young adults with severe haemophilia: a qualitative study with healthcare professionals. Issue 1 (1st January 2020) - van Os, S.; Ryder, N.; Hart, D. P.; Troop, N.
ABSTRACT: Aim: to examine healthcare professionals' (HP) perceptions and experiences in relation to adherence to prophylactic treatment among young people living with haemophilia (YPH). Methods: All HPs in four haemophilia centres across England and Wales were invited to participate, and all HPs who agreed to take part ( n  = 6) were interviewed. Interviews were audio-recorded, transcribed and then analysed using Interpretative Phenomenological Analysis (IPA). Results: HPs estimate that generally young people with haemophilia keep to their treatment regimen well, although they also recognise that adherence may fluctuate with many patients going through shorter periods of non-adherence. The increasingly personalised or flexible approach to prophylaxis makes it harder to assess adherence. The main themes identified through IPA included (1) HPs' suggest that adherence fluctuates (2) Non-adherence is mainly driven by lifestyle and developmental, social and family factors, and (3) Education, HPs' sensitivity to individual needs, and psychological and peer support are key facilitators of good adherence. Conclusion: The increasingly flexible approach to prophylaxis requires a new way of thinking about, and assessment of, adherence. More personalised treatment regimen can be more complicated and may, therefore, lead to accidental non-adherence. The results of this study with HPs complement those of a previous qualitative study with patients but place greater emphasis on a broader perspective on understanding drivers of non-adherence as well as understanding strategies to improve adherence in the minority of patients who appear to struggle.